Dynamic Amplitude Prediction for Ballroom Floors - Hanagan, Linda M. (Engineering Journal, 2002)
To avoid excessive vibration in ballroom-type floors, engineers can evaluate a floor system design before construction using the procedures outlined in the AISC Design Guide 11. These procedures are most appropriately applied to simply supported beam systems where dancing is expected to occur over the entire span. This paper presents a modification to assess beam/girder systems subjected to dance type loads over only a portion of the bay. This modification is especially useful for long-span systems where meeting the serviceability requirements is difficult.